Integrated management of root-knot nematode (Meloidogyne incognita) in potato - S.M. CHAUDHARI and D.J. PATEL, NARENDRA SINGH*, M.N. MAHESHWARI (Indian Phytopathology, 2014)
Root-knot nematode (Meloidogyne incognita) infection on potato crop is prevailing in many potato growing states including Gujarat in India and render 30-40% produce unfit for sale. An experiment on integrated management was conducted in nematode infested farmer field. The results of two years pooled data revealed that soil application of carbofuran @ 1 kg/ha (Furadan 3 G @ 33 kg/ha) along with bio agent P. lilacinus @ 5 kg/ha enriched with FYM (farm yard manure) at planting time recorded minimum numbers of wilted plants (0.2) with minimum nematode infected tubers (0.62 t/ha) with least root-knot index (0.44) in 0-5 scale. The same treatment also recorded significantly highest healthy tubers yield (23.91t/ha) with net realization of Rs. 33,375/ha giving ICBR 1: 9.60 over untreated control.